$$I=(-1)^{n-1}{m\over n+m}\int_{0}^{1}x^{n-1}(1-x)^{m-1}dx=\sum_{i=0}^{n}(-1)^i{n\choose i}H_{n+m-i}\tag1$$ Where $H_n$ is the nth harmonic number


$$H_n=\int_{0}^{1}{1-x^n\over 1-x}dx\tag2$$

Sub $(2)$ into $(1)\rightarrow (3)$

$$I=\sum_{i=0}^{n}(-1)^i{n\choose i}\int_{0}^{1}{1-x^{n+m-i}\over 1-x}dx\tag3$$

Let $$J=\int_{0}^{1}{1-x^{n+m-i}\over 1-x}dx\tag4$$


$$J=\sum_{k=0}^{\infty}\left({1\over k+1}-{1\over k+1+n+m-i}\right)\tag6$$

Can someone help me here to prove I, don't seem to have a clue where I am going?

  • 1
    $\begingroup$ Use $H_n=\int\limits_0^1 \frac{1-(1-x)^n}{x}dx$ instead of (2). $\endgroup$ – user90369 Jun 9 '16 at 13:17
  • $\begingroup$ Out of curiosity, what is the source of all these problems? $\endgroup$ – Jack D'Aurizio Jun 9 '16 at 13:50
  • $\begingroup$ You mean where did I get them from or what is the point of me posting these problems? $\endgroup$ – gymbvghjkgkjkhgfkl Jun 9 '16 at 14:24
  • $\begingroup$ @China cat: Have you solved the problem with the hint above ? It's not difficult. $\endgroup$ – user90369 Jun 9 '16 at 17:02

I think that you can not use this approach because $${1\over k+1}-{1\over k+1+n+m-i}={1\over k+1}-{1\over k+2}+{1\over k+2}-{1\over k+3}+...+{1\over k+1+n+m-i-1}-{1\over k+1+n+m-i}$$ $$J=1+\frac{1}{2}+\frac{1}{3}+...+{1\over 1+n+m-i-1}= \sum\limits_{j=1}^{1+m+n-i-1}{\frac{1}{j}} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.